Derivation of Two New Human Embryonic Stem Cell Lines from Nonviable Human Embryos - Svetlana Gavrilov; Darja Marolt; Nataki C. Douglas; Robert W. Prosser; Imran Khalid; Mark V. Sauer; Donald W. Landry; Gordana Vunjak-Novakovic; Virginia E. Papaioannou (Stem Cells International)
We report the derivation and characterization of two new human embryonic stem cells (hESC) lines (CU1 and CU2) from embryos with an irreversible loss of integrated organismic function. In addition, we analyzed retrospective data of morphological progression from embryonic day (ED) 5 to ED6 for 2480 embryos not suitable for clinical use to assess grading criteria indicative of loss of viability on ED5. Our analysis indicated that a large proportion of in vitro fertilization (IVF) embryos not suitable for clinical use could be used for hESC derivation. Based on these combined findings, we propose that criteria commonly used in IVF clinics to determine optimal embryos for uterine transfer can be employed to predict the potential for hESC derivation from poor quality embryos without the destruction of vital human embryos.